2017
DOI: 10.1177/2047487317724008
|View full text |Cite
|
Sign up to set email alerts
|

Associations between alcohol consumption and cardio-metabolic risk factors in young adults

Abstract: Introduction The benefits of alcohol consumption for cardiovascular and metabolic health may have been overstated due to inappropriate comparisons with abstainers and inadequate control for confounding factors including physical activity and mental health. We examined alcohol consumption and cardio-metabolic health in a cohort of young Australian adults overcoming these limitations. Methods Cross-sectional data of a cohort of 2200 participants (age range 25-36 years) from the 2004-06 Childhood Determinants of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
1
16
0
1
Order By: Relevance
“…In a cross‐sectional study, Gillman and colleagues () found that young adults (18 to 26 years of age) consuming no alcohol and <1 drink/d over the last 30 days had a 4 mm Hg higher in systolic blood pressure compared with those who consumed 1 to <2 drinks/d. In young adults (26 to 36 years) enrolled in the 2004 to 2006 follow‐up of the Childhood Determinants of Adult Health, Du and colleagues () found systolic blood pressure was similar among nondrinkers (116 ± 13 mmHg), light drinkers (>0 to 1 drink/d; 117 ± 12 mmHg), and moderate drinkers (>1 to 2 drinks/d; 120 ± 13 mmHg). Collectively, these findings suggest that low‐to‐moderate levels of alcohol consumption in young adults do not increase the risk for elevated blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…In a cross‐sectional study, Gillman and colleagues () found that young adults (18 to 26 years of age) consuming no alcohol and <1 drink/d over the last 30 days had a 4 mm Hg higher in systolic blood pressure compared with those who consumed 1 to <2 drinks/d. In young adults (26 to 36 years) enrolled in the 2004 to 2006 follow‐up of the Childhood Determinants of Adult Health, Du and colleagues () found systolic blood pressure was similar among nondrinkers (116 ± 13 mmHg), light drinkers (>0 to 1 drink/d; 117 ± 12 mmHg), and moderate drinkers (>1 to 2 drinks/d; 120 ± 13 mmHg). Collectively, these findings suggest that low‐to‐moderate levels of alcohol consumption in young adults do not increase the risk for elevated blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Results are still significant after adjusting for potential confounders, including physical activity (PA), cardiorespiratory fitness and mental health. 8 However higher levels of alcohol consumption are associated with higher blood pressure, confirming the detrimental effect. Therefore, health promotion messages should convey both the positive and negative effects of alcohol on the cardiometabolic and general health of young people.…”
Section: Alcohol Consumptionmentioning
confidence: 92%
“…Наконец, при обсуждении возможных путей развития АКМП необходимо помнить о том, что злоупотребление алкоголем может приводить к развитию других сердечно-сосудистых заболеваний, каждое из которых способно вызывать изменения сердечной мышцы: артериальная гипертония, стабильная стенокардия, нарушения ритма сердца. Также у лиц, злоупотребляющих алкоголем, часто встречаются нарушения липидного обмена, в особенности гипертриглицеридемия, и другие признаки метаболического синдрома [46,47]. Поражение сердца у пациентов с тяжелыми хроническими заболеваниями печени получило название цирротической КМП, характеризующейся повышением сердечного выброса с последующей систолической и диастолической дисфункцией ЛЖ, хотя не все случаи цирротической КМП имеют алкогольный генез [48].…”
Section: патогенезunclassified